Solar Energy Conversion Methods - SOBCZYK, WIKTORIA; NAGORNIUK, OKSANA; RIABUSHENKO, OLGA; WLIZŁO, JAKUB (Journal of Education, Technology and Computer Science, 2018)
This article presents the characteristics of three basic methods of solar energy conversion: thermal energy – photothermal conversion, electrical energy – photovoltaic conversion, energy related to chemical processes – photochemical conversion. The paper addresses some aspects of the primary goals of EU climate and energy policy, as well as the benefits of passive building constructions.